2023
DOI: 10.2196/47821
|View full text |Cite
|
Sign up to set email alerts
|

Rosacea and Its Association With Malignancy: Systematic Review

Luna Thapa,
Joyce Xia,
William Guo
et al.

Abstract: Background Rosacea is a chronic inflammatory skin condition that predominantly manifests as facial flushing, irritation, and acne. Rosacea and cancer are thought to be linked by the commonality of inflammatory and immune response dysfunction. Studies that have looked into this possible association have reported mixed results. Objective Given the conflicting literature on this topic, our study sought to evaluate the overall association between rosacea an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Cancer is a major systemic disorder with imbalanced inflammatory and immune response as a hallmark. Similarly, the pathogenesis of rosacea is known to involve an abnormal inflammatory response, indeed, studies have reported a higher incidence of cancer in rosacea patients 10 . For example, Egeberg et al 19 .…”
Section: Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer is a major systemic disorder with imbalanced inflammatory and immune response as a hallmark. Similarly, the pathogenesis of rosacea is known to involve an abnormal inflammatory response, indeed, studies have reported a higher incidence of cancer in rosacea patients 10 . For example, Egeberg et al 19 .…”
Section: Disscussionmentioning
confidence: 99%
“…Similarly, the pathogenesis of rosacea is known to involve an abnormal inflammatory response, indeed, studies have reported a higher incidence of cancer in rosacea patients. 10 For example, Egeberg et al. 19 conducted an epidemiological study to investigate the cancer incidence in patients previously diagnosed with rosacea with that in the general population, their 4‐year follow‐up revealed an elevated risk of non‐melanoma skin cancer (NMSC), breast cancer and hepatic cancer among patients with of rosacea.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation